Mechatronics : a foundation course - De Silva, Clarence W. (Boca Raton, FL : CRC Press, 2010)
"This book explains the fundamentals of integrating different types of components and functions, both mechanical and electrical, to achieve optimal operation that meets a desired set of performance specifications. This integration will benefit performance, efficiency, reliability, cost, and environmental impact."--Publisher description.
Mechatronic engineering -- Basic elements and components -- Modeling of mechatronic systems -- Component interconnection and signal conditioning -- Instrument ratings and error analysis -- Sensors and transducers -- Actuators -- Digital hardware and microcontrollers -- Control systems -- Case studies in mechatronics -- Appendix A : Solid mechanics -- Appendix B : Transform techniques -- Appendix C : Probability and statistics -- Appendix D : Software tools.
Includes bibliographical references and index.
Keywords: Mechatronics